Inability to perform the five-chair stand test predicts increased risk of sarcopenia in nursing home residents - Martin Šporin; Dorjana Zerbo Šporin (Exercise and Quality of Life)
The proportion of elderly and sarcopenia cases is expected to increase in the coming decades. Early diagnosis of sarcopenia using muscle strength as a criterion is important to prevent adverse health effects. The repetitive chair stand test is an effective tool for assessing muscle strength. Poor test performance may indicate an individual with potential sarcopenia. The aim of this study was to investigate the effect of the ability to perform the five-repetition chair stand test on the prevalence of sarcopenia in residents of western Slovenian nursing homes. 83 candidates (age 83.8±7.6 years, 69% of whom were women) we included in the study. The prevalence of sarcopenia was determined according to European Working Group for Sarcopenia guidelines and the five-repetition chair stand test was used to assess physical performance. Relative risk with a 95% confidence interval was calculated to assess the difference in risk for sarcopenia between the complete rises and the incomplete rises group. 37% of participants were diagnosed as sarcopenic, of whom approximately half were unable to complete the 5-chair stand test. The risk of sarcopenia was twice as high in participants who were unable to complete the test (RR = 2.05 (CI 1.21-3.49); p=0.0077). The inability to complete the repeated chair stand test in older adults from nursing homes significantly increases the risk of sarcopenia. Therefore, this test could be useful in identifying individuals at high risk.